Feasibility and perioperative outcomes of percutaneous-assisted laparoscopic hysterectomy: A multicentric Italian experience. (February 2020) - Gueli Alletti, Salvatore; Perrone, Emanuele; Cretì, Antonio; Cianci, Stefano; Uccella, Stefano; Fedele, Camilla; Fanfani, Francesco; Palmieri, Stefano; Fagotti, Anna; Scambia, Giovanni; Rossitto, Cristiano
Abstract: Objective: This multicentric prospective phase II study aimed to investigate the feasibility, safety, and efficacy of percutaneous-assisted laparoscopic hysterectomy in terms of perioperative outcomes, feasibility, VAS score, and cosmetic outcomes. Study Design: Between May 2015 and October 2017, 382 patients were considered eligible for minimally invasive percutaneous-assisted laparoscopic hysterectomy using Percuvance™, Percutaneous Surgical System - PSS, TELEFLEX ltd. Among them, 80 patients (20.9 %) met the inclusion criteria and were enrolled in the study. The coordinator center was the Division of Gynecologic Oncology, Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome, Italy. Enrolled patients underwent total percutaneous-assisted laparoscopic hysterectomy ± bilateral salpingo-oophorectomy ± nodal assessment. Results: The median age was 52 (range, 32–80) years, and the median body mass index was 25 kg/m 2 (range, 16–37). Thirty-five patients (43.8 %) had previous surgery. A median operative time of 82.5 (range, 40–190) minutes and a median estimated blood loss of 50 (50–500) mL were registered. We observed 1 (1.3 %) intraoperative complication. The median time to discharge was 1 (range, 1–5) day. Patients were extremely satisfied with the scar evaluation and postoperative pain control. Five (6.25 %) complications were recorded within 30 days after surgery. Conclusion: Percutaneous-assisted technique for extrafascial hysterectomy achieved excellent results in terms of feasibility, safety, and efficacy, even in complex cases and advanced surgical procedures. Therefore, the technique appears to balance the limitations and advantages of minimal surgical invasiveness and standard approach efficacy.